Neuroprotective effects of tualang honey in male rats exposed to normobaric hypoxia - Abdo Qaid , Entesar Yaseen (2017)
Exposure to environmental hypoxia can induce memory impairment and oxidative stress is thought to be one of the underlying mechanisms. The potential effects of natural products with antioxidant properties to enhance cognitive function have been the focus of many researches nowadays. Thus, the present study aims to evaluate the effect of normobaric hypoxia on memory performance and elucidate the potential mechanisms of Tualang honey in improving hypoxia-induced memory impairment in adult male rats. Forty-eight male Sprague-Dawley rats were divided into four groups: 1) sucrose treated non-hypoxia, 2) honey treated non-hypoxia, 3) sucrose treated hypoxia, 4) honey treated hypoxia. The honey was administered orally, 0.2 g/kg for 14 days before exposure to hypoxia. All experimental animals were subjected to novel object recognition task (NORT) and T-maze twice i.e. prior to honey treatment and after exposure to hypoxia. Rats were exposed to hypoxia by placing them in a hypoxic chamber at O2 content of 11%. After completion of the experiment, the rats were sacrificed. Their blood and brain samples were collected.The right brain hemispheres were fixed 10% formalin for histological study of the hippocampal region. The left brain hemispheres were homogenised, centrifuged and used for analysis of catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD), total antioxidant capacity (TAC) and malondialdehyde (MDA) levels/activities using enzyme-linked immunosorbent assay (ELISA) technique. Serum corticosterone was measured using commercially available ELISA kits. The findings from the present study showed significant effects of hypoxia exposure on impairment of memory performance, decrease in number of pyramidal cells in all hippocampal regions, decrease in levels and activities of antioxidant enzymes and increase in MDA in the brain homogenate, and serum corticosterone level in sucrose treated hypoxia group compared to other experimental groups (P<0.05). Improved memory performance, increased levels/activities of brain TAC, CAT, GPx and SOD, reduced brain MDA and serum corticosterone levels, prevented neuronal cells apoptosis in all hippocampal regions in honey treated hypoxia group compared to sucrose treated hypoxia group (P<0.05). In conclusion, Tualang honey pre-treatment at a dose of 0.2 g/kg for 14 days has the potential to be used as an alternative therapy to protect against hypoxia-induced memory impairment.